How Many Twists Do Solar Coronal Jets Release? - Liu, Jiajia; Wang, Yuming; Erdélyi, Robert (Frontiers in Astronomy and Space Sciences, 2019)
Highly twisted magnetic flux ropes, with finite length, are subject to kink instabilities, and could lead to a number of eruptive phenomena in the solar atmosphere, including flares, coronal mass ejections (CMEs) and coronal jets. The kink instability threshold, which is the maximum twist a kink-stable magnetic flux rope could contain, has been widely studied in analytical models and numerical simulations, but still needs to be examined by observations. In this article, we will study twists released by 30 off-limb rotational solar coronal jets, and compare the observational findings with theoretical kink instability thresholds. We have found that: 1) the number of events with more twist release becomes less; 2) each of the studied jets has released a twist number of at least 1.3 turns (a twist angle of 2.6$π$); and 3) the size of a jet is highly related to its twist pitch instead of twist number. Our results suggest that the kink instability threshold in the solar atmosphere should not be a constant. The found lower limit of twist number of 1.3 turns should be merely a necessary but not a sufficient condition for a finite solar magnetic flux rope to become kink unstable.